Evolution of sex chromosomes prior to speciation in the dioecious Phoenix species. (20th May 2016) - Cherif, E.; Zehdi Azouzi, S.; Crabos, A.; Castillo, K.; Chabrillange, N.; Pintaud, J.‐C.; Salhi‐Hannachi, A.; Glémin, S.; Aberlenc‐Bertossi, F.
Abstract: Understanding the driving forces and molecular processes underlying dioecy and sex chromosome evolution, leading from hermaphroditism to the occurrence of male and female individuals, is of considerable interest in fundamental and applied research. The genus Phoenix, belonging to the Arecaceae family, consists uniquely of dioecious species. Phylogenetic data suggest that the genus Phoenix has diverged from a hermaphroditic ancestor which is also shared with its closest relatives. We have investigated the cessation of recombination in the sex‐determination region within the genus Phoenix as a whole by extending the analysis of P .  dactylifera SSR sex‐related loci to eight other species within the genus. Phylogenetic analysis of a date palm sex‐linked PdMYB1 gene in these species has revealed that sex‐linked alleles have not clustered in a species‐dependent way but rather in X and Y‐allele clusters. Our data show that sex chromosomes evolved from a common autosomal origin before the diversification of the extant dioecious species.